2020
DOI: 10.1155/2020/4204987
|View full text |Cite
|
Sign up to set email alerts
|

A 7-Year Trend of Malaria at Primary Health Facilities in Northwest Ethiopia

Abstract: Background. Malaria is a severe parasitic disease that can progress to complications of the nervous system, respiratory distress, renal problems, metabolic acidosis, and hypoglycemia which can result in death in case of delay or absence of appropriate treatment. Even though health service facilities and vector control strategy in the community are implemented as control measures, variations in temperature and rainfall that can affect the life cycle of parasite are among the factors of malaria prevalence over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

31
23
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 13 publications
31
23
6
Order By: Relevance
“…In this particular study, the highest cases of malaria were observed during spring (September, October and November). The seasonality observed in the current study is in agreement with studies in different parts of Ethiopia [ 21 23 ], all of which revealed high malaria transmission periods corresponding to the months of September, October and November. In most parts of Ethiopia, the main malaria transmission season is from September to December, following the rainiest season from June to September [ 1 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this particular study, the highest cases of malaria were observed during spring (September, October and November). The seasonality observed in the current study is in agreement with studies in different parts of Ethiopia [ 21 23 ], all of which revealed high malaria transmission periods corresponding to the months of September, October and November. In most parts of Ethiopia, the main malaria transmission season is from September to December, following the rainiest season from June to September [ 1 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present retrospective data analysis, malaria prevalence trend appeared to be non-fluctuating, in which the malaria positivity rate continued to show consistent decline in the past five years. This finding is congruent with similar studies from several malaria endemic areas of Ethiopia which reported a decrease in malaria prevalence from 2001 to 2016 [2,17,21,22]. Ethiopia has been implementing key malaria interventions, including use of insecticide treated net (ITN) and indoor residual spraying (IRS), prompt diagnosis and treatment with artemisinin-based combination therapy, intermittent preventive treatment in pregnancy and environmental management in integrated manner throughout the country since 2005 [1].…”
Section: Discussionsupporting
confidence: 83%
“…In the present retrospective data analysis, malaria prevalence trend appeared to be non-uctuating, in which the malaria positivity rate continued to show consistent decline in the past ve years. This nding is congruent with similar studies from several malaria endemic areas of Ethiopia which reported a decrease in malaria prevalence from 2001 to 2016 [2,17,[21][22]. Ethiopia has been implementing key malaria interventions, including use of insecticide treated net (ITN) and indoor residual spraying (IRS), prompt diagnosis and treatment with artemisinin-based combination therapy, intermittent preventive treatment in pregnancy and environmental management in integrated manner throughout the country since 2005 [1].…”
Section: Discussionsupporting
confidence: 81%
“…However, the index study was conducted on children admitted generally for various conditions, thereby making the prevalence of malaria less in such a situation. Several previous reports have also documented that overwhelming majority of childhood malaria occur in children <5 years [19,20]. Results of our study are in accordance with the previous reports, wherein we found 85.1% prevalence rates in children aged <5 years.…”
Section: Discussionsupporting
confidence: 93%
“…The infant develops its own active immunity gradually and progressively from the later part of the 1 st year. However, the infant is prone to increasing attacks of malaria until about the age of 5 when the immunity develops adequately to curb significantly the prevalence and severity of malaria attacks [20]. At a young age, without the adult supervision, the child is unable to exercise self-protective measures such as moving to more secured places, away from a place of exposure to mosquito bite, despite the discomfort of the experience, wearing protective clothing, mosquito repellant creams, shut access of mosquitoes to living room, and apply insecticide treated bed nets, thereby making the child more predisposed to malaria attacks.…”
Section: Discussionmentioning
confidence: 99%